8 Documents and Records Relating to the State of New Hampshire During the Period of the American Revolution from 1776-1783 at 15-16 (nathaniel Bouton ed.1874), Jan 12, 1775. - (:unkn) unknown (General Publisher, 1775)
Requiring each firearm sold in the colony to possess certain specifications and pass inspection involving the safe firing of the gun.
--
Keywords: MANUFACTURE ONLY